2016
DOI: 10.1016/j.neuroimage.2015.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Anterior insula coordinates hierarchical processing of tactile mismatch responses

Abstract: The body underlies our sense of self, emotion, and agency. Signals arising from the skin convey warmth, social touch, and the physical characteristics of external stimuli. Surprising or unexpected tactile sensations can herald events of motivational salience, including imminent threats (e.g., an insect bite) and hedonic rewards (e.g., a caressing touch). Awareness of such events is thought to depend upon the hierarchical integration of body-related mismatch responses by the anterior insula. To investigate this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 65 publications
17
100
0
Order By: Relevance
“…This study has examined the impact of singing training on insula-based network connectivity. The results of this research support the idea that the insula plays a central role in modulating sensory integration within the vocal system (Cloutman et al, 2012;Nieuwenhuys, 2012;Parkinson et al, 2012), perhaps by regulating conscious and non-conscious aspects of salience processing associated with singing-related bodily processes (Allen et al, 2016;Chong et al, 2017). This may optimize the processing, manipulation, and transformation of sensory information based on experience (Zarate, 2013;Zarate and Zatorre, 2005).…”
Section: Discussionsupporting
confidence: 74%
“…This study has examined the impact of singing training on insula-based network connectivity. The results of this research support the idea that the insula plays a central role in modulating sensory integration within the vocal system (Cloutman et al, 2012;Nieuwenhuys, 2012;Parkinson et al, 2012), perhaps by regulating conscious and non-conscious aspects of salience processing associated with singing-related bodily processes (Allen et al, 2016;Chong et al, 2017). This may optimize the processing, manipulation, and transformation of sensory information based on experience (Zarate, 2013;Zarate and Zatorre, 2005).…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, our meta-analyses indicated that the region associated with Personal Distress is involved in affective processing, as part of the salience network. More specifically, the observed negative relationship between insula myelination and Personal Distress may depend on the role of the insula as an integrative emotional hub5758. This could arise either because reduced insula myelination dysregulates incoming visceral and somatic inputs (e.g., a bottom-up effect), or disrupts the ability to cognitively re-appraise or regulate responses to other’s emotions.…”
Section: Discussionmentioning
confidence: 99%
“…2C). The right AI cortex anticipates the sensory and affective consequences of touch [Lovero et al, 2009], yet functional asymmetry of the insula has also been ascribed to differences in ascending and descending connections [Allen et al, 2016;Bastos et al, 2015]. Intriguingly, unique functions have been ascribed to the right ventral AI [Craig, 2009a;Critchley et al, 2004; , 2013;Nieuwenhuys, 2012;Seeley et al, 2011;Uddin, 2014], based on a unique abundance of von Economo neurons (VENs) in both the right ventral AI and the ACC (Seeley et al, 2011).…”
Section: The Anterior Insula In Musiciansmentioning
confidence: 99%